2013
DOI: 10.1073/pnas.1308209110
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of A 2A receptors potently suppresses the metastasis of CD73 + tumors

Abstract: CD73 inhibits antitumor immunity through the activation of adenosine receptors expressed on multiple immune subsets. CD73 also enhances tumor metastasis, although the nature of the immune subsets and adenosine receptor subtypes involved in this process are largely unknown. In this study, we revealed that A 2A /A 2B receptor antagonists were effective in reducing the metastasis of tumors expressing CD73 endogenously (4T1.2 breast tumors) and when CD73 was ectopically expressed (B16F10 melanoma). A 2A −/− mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
302
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 307 publications
(323 citation statements)
references
References 45 publications
10
302
1
Order By: Relevance
“…Notably, our findings that A 2A blockade can enhance the activity of anti-PD-1 are supported by the recent study by Sitkovsky and colleagues who showed that the removal of the hypoxic (adenosine promoting) environment could enhance the activity of dual PD-1 and CTLA-4 blockade in an A 2A dependent manner. 7 Although our data supports a number of studies showing that blockade of the A 2A receptor enhances antitumor immunity, 3,[5][6][7] it has recently been observed that genetic ablation of A 2A can be deleterious in some tumor models due to reduced T cell effector memory differentiation/ survival. 8 Therefore, it may be that the pharmacodynamic and pharmacokinetic properties of A 2A antagonists are vital to their therapeutic outcome.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Notably, our findings that A 2A blockade can enhance the activity of anti-PD-1 are supported by the recent study by Sitkovsky and colleagues who showed that the removal of the hypoxic (adenosine promoting) environment could enhance the activity of dual PD-1 and CTLA-4 blockade in an A 2A dependent manner. 7 Although our data supports a number of studies showing that blockade of the A 2A receptor enhances antitumor immunity, 3,[5][6][7] it has recently been observed that genetic ablation of A 2A can be deleterious in some tumor models due to reduced T cell effector memory differentiation/ survival. 8 Therefore, it may be that the pharmacodynamic and pharmacokinetic properties of A 2A antagonists are vital to their therapeutic outcome.…”
supporting
confidence: 84%
“…3 CD73 is an ectoenzyme which suppresses the antitumor immune response due to its conversion of AMP to adenosine which consequently suppresses immune responses due to the activation of A 2A and A 2B receptors on a wide range of immune cells including T lymphocytes. 5 Targeting this pathway by either direct inhibition of CD73 or the downstream A 2A /A 2B receptors has been shown to induce antitumor immunity 3,6,7 (and reviewed by Leone et al 5 ).…”
mentioning
confidence: 99%
“…At first sight, the inhibitory effects of adenosine are unexpected because high ecto-5 0 -nucleotidase activity is often considered as a poor prognostic factor, which allows the tumors to avoid immune destruction via the generation of immunosuppressive adenosine and deactivation of tumorinfiltrating inflammatory cells (5,10,12,32). This apparent discrepancy could be resolved on the basis of the following considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Ã , P < 0.05, as compared with control. For complete densitometric analyses of phospho-kinases in control and adenosine-treated PC-3, cells see Supplementary Table. Therefore, local and transient generation of nanomolar adenosine by tumor-derived CD73 would indeed be sufficient for the failure of mounting effective immune responses via activation of the A 2A receptors on cytotoxic T lymphocytes and other inflammatory cells (14,32). On the other hand, the overall pattern of purine homeostasis is markedly deregulated in the tumor environment by hypoxia and metabolic stress, as ascertained by data on constitutively elevated levels of intratumoral ATP (7,34), the accelerated rate of nucleotide turnover (4,9,33), and the ability of solid tumors to maintain adenosine gradient, with the highest nucleoside concentrations being reported in the center (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation